Autovaloración de calidad de vida y envejecimiento en adultos con riesgo de Alzheimer (2008)
ABSTRACT: middle-age adult carriers and non-carriers of mutation E280A in gene Presenilin 1 for Early Onset Familial Alzheimer’s Disease and of elderly adults in Antioquia-Colombia. Study conducted from January 2005 to June 2007. Methodology: descriptive transversal study in which 162 asymptomatic people at risk of developing Alzheimer’s disease as a genetic consequence or as a consequence of the process of aging. They were subdivided into three groups: 27 carriers of the mutation, 39 non-carriers and 96 elderly adults. The study was conducted at the Neuroscience Group in Medellín (Antioquia) and at a gerontology center in Envigado (Antioquia) named Atardecer. Social-demographic characteristics were analyzed and quality of life and overall aging selfassessment tests were applied, which included the World Health Organization Quality of Life, and the Nürnberg -Self-Evaluation-List respectively. Statistic Analysis: The groups were described and they were compared to the variables of the study using Kruskall Wallis non-parametric ANOVA and Mann-Whitney’s U-test. Results: the mean scores of the instruments to assess quality of life and overall aging of three groups of participants were above 50 points and below 55 points respectively. Conclusions: elderly adults assessed themselves as having a lower quality of life than carriers and non-carriers, especially in the physical health area, and in their perception of aging, in spite of carriers’ conditions, although in general the scores were good in all the groups.